2018
DOI: 10.11604/pamj.2018.30.96.12818
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by marginalized communities such as transgenders in Pakistan

Abstract: IntroductionStigmatization, social exclusion and consequent banishment from the society makes transgender's life even tougher; isolating, pushing and forcing them into inappropriate conducts/habits like selling sex. This study investigates the association of social exclusion/victimization with high-risk behaviors among transgender community of Rawalpindi and Islamabad (Pakistan).MethodsThrough a cross-sectional study design, a sample of 189 transgender community living in twin cities of Rawalpindi and Islamaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In the UK, the number of transphobic hate crimes reported annually has tripled since 2014 and a survey of trans youth in Scotland found that 73% of respondents reported experiencing at least one type of specifically transphobic emotionally abusive behavior from a current or ex-partner (LGBT Youth J o u r n a l P r e -p r o o f up to an estimated 89% of trans people are at risk of gender-based violence (Wirtz, Poteat, Malik, & Glass, 2018). Prior research has strongly associated surviving violence of this nature with increased rates of alcohol (Arayasirikul, Wilson, & Raymond, 2017;Chakrapani, Newman, Shunmugam, Logie, & Samuel, 2017;Nuttbrock et al, 2014) and illicit drug use (Budhwani et al, 2017;Scheim, Bauer, & Shokoohi, 2017;Shah et al, 2018), as well as nonmedical use of prescription drugs (Benotsch et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, the number of transphobic hate crimes reported annually has tripled since 2014 and a survey of trans youth in Scotland found that 73% of respondents reported experiencing at least one type of specifically transphobic emotionally abusive behavior from a current or ex-partner (LGBT Youth J o u r n a l P r e -p r o o f up to an estimated 89% of trans people are at risk of gender-based violence (Wirtz, Poteat, Malik, & Glass, 2018). Prior research has strongly associated surviving violence of this nature with increased rates of alcohol (Arayasirikul, Wilson, & Raymond, 2017;Chakrapani, Newman, Shunmugam, Logie, & Samuel, 2017;Nuttbrock et al, 2014) and illicit drug use (Budhwani et al, 2017;Scheim, Bauer, & Shokoohi, 2017;Shah et al, 2018), as well as nonmedical use of prescription drugs (Benotsch et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, Muslims, in general, perceive transgender people as intersex, homosexuals, or suffering from mental health issues. 19 , 20 This is contrary to the basic scientific knowledge and understanding of the condition, that is, transgender people suffer from gender identity or expression issue and are not the same as intersex. 2 , 3 , 21 There have been reports that adolescents or adults who identified themselves as transgender are mocked for being intersex, and suffered emotional and physical persecution for being mistaken as homosexuals.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is critical to note that no major attempts have been made to attain a prevalence of intersex individuals in Pakistan. Many experts say that the actual number of transgender people is substantially higher than what Shah et al (2018) revealed in their census report. The estimate was about that about 10418 individuals in Pakistan are transgender which make about 0.0048 % of the population.…”
Section: Introductionmentioning
confidence: 89%